Trauma Tokoh Utama Wanita Dalam Novel Lamising Katresnan Karya Budiono Santoso Setradjaja (Kajian Psikoanalisis Sigmund Freud) - Elisa Candra Engelita (Jurnal Online Baradha, 2025)
Abstract The trauma experienced by the female protagonist has a significant impact on her emotional and psychological development. As a result of the trauma, the female protagonist's id is very dominant so that the ego tries hard to balance basic desires, moral demands, and reality by carrying out several protection mechanisms. Therefore, the purpose of this study is to determine the form of trauma experienced by the female protagonist and the defense mechanisms carried out to overcome the trauma. This study uses a qualitative method that is more focused on the narrative analysis approach using Sigmund Freud's psychoanalytic theory. The data sources for this study are divided into two, namely primary data sources and secondary data sources. The primary data source is a Javanese novel entitled Lamising Katresnan which was published in 2023. While the secondary data sources are in the form of journals, books, previous research that is in accordance with the research topic. The results of this study indicate that the form of trauma experienced by the female protagonist is situational trauma caused by rape, rape in marriage, and loss of a loved one. Then the ego defense mechanisms carried out are sublimation, rationalization, rejection/denial, and repression. Keywords: Trauma, Sigmund Freud’s psychoanalytic, Sexuality, Defense mechanisms